The Industrial Organization of Banking Bank Behavior, Market Structure, and Regulation - VanHoose, David (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides an evaluation of the industrial organization of banking with a focus on the interrelationship among bank behavior, market structure, and regulation. It addresses a wide range of public policy topics, including bank competition and risk, international banking, antitrust issues, and capital regulation. New to this edition, which has been updated throughout, is a broadened consideration of alternative theories of competition among banks, which includes discussions of such issues as the implications of large increases in bank reserve holdings in recent years, effects of nonprice competition through quality rivalry, analysis of mixed market structures involving both large and small banks, and international interactions of banks and policymakers. The intent of the book is to serve as a learning tool and reference for graduate students, academics, bankers, and policymakers seeking to better understand the industrial organization of the banking sector and the effects of banking regulations.
Keywords: Financial services industry; Industrial organization; Business enterprises-Finance.; Financial Services; Industrial Organization; Corporate Finance